Economics Explained: Everything You Need to Know About How the Economy Works and Where It's Going - Robert L Heilbroner (A Touchstone Book /Simon & Schuster, 1998)
Captialism: where do we come from? -- Three great economists -- A bird's-eye view of the economy -- The trend of things -- The GDP -- Saving and investing -- Passive consumption, active investment -- The economics of the public sector -- The debate about government -- What money is -- How money works -- How markets work -- Where markets fail -- The two worlds of business -- The specter of inflation -- The inequallity problem -- Globalization -- National policy in the globalized world -- The unfinished revolution.